The transformation of countryside into a dispersed city: a critical local-scale analysis of selected Polish suburbs - Wdowiarz-Bilska, Matylda; Ciepiela , Agnieszka; Łabuz, Rita (Bulletin of Geography. Socio-economic Series, 2024)
The purpose of this article is to highlight the main challenges presented by the spatial transformation of countryside as a result of strong investment pressure in the metropolitan zones of selected Polish cities. The research focuses on the spatial structures of selected communes adjacent to Warsaw, Kraków and Lublin. The study deals with the problem of spatial transformations of the rural landscape. This was done on the background of socio-economic redevelopment and demographic changes. The results show a significant investment pressure and identify the stages and forms of spatial development characterising urbanisation in the studied suburban areas in recent years. The author’s planning concept is proposed as an example of a tool for controlling excessive dispersal at local and regional levels.